2004
DOI: 10.1002/chin.200424009
|View full text |Cite
|
Sign up to set email alerts
|

Ternary System Tm—Cu—Ge: Isothermal Section of the Phase Diagram at 870 K and Crystal Structures of the Compounds.

Abstract: Structure Structure D 2000Ternary System Tm-Cu-Ge: Isothermal Section of the Phase Diagram at 870 K and Crystal Structures of the Compounds. -Four ternary compounds are identified in the 870 K isothermal section of the title system and their structures are determined by Rietveld refinement of powder XRD data. The known compounds TmCu2Ge2, Tm2CuGe6, and Tm6Cu8Ge8 crystallize in the space groups I4/mmm, Amm2, and Immm, respectively. The new ternary copper germanide TmCu 1.24 Ge 0.76 crystallizes in the hexagonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…These problems may have hindered identification of the 124 structure in past surveys: Materials having exact 124 formula has not been reported so far in R-Co-Ge system. However, Tm 0.15 Co 0.30 Ge 0.55 was previously observed during a Tm-Co-Ge ternary phase diagram study as one of compounds with unknown structures [16], We guess that the reported Tm 0.15 Co 0.30 Ge 0.55 was identical to our 124 compound.…”
Section: Methodssupporting
confidence: 64%
“…These problems may have hindered identification of the 124 structure in past surveys: Materials having exact 124 formula has not been reported so far in R-Co-Ge system. However, Tm 0.15 Co 0.30 Ge 0.55 was previously observed during a Tm-Co-Ge ternary phase diagram study as one of compounds with unknown structures [16], We guess that the reported Tm 0.15 Co 0.30 Ge 0.55 was identical to our 124 compound.…”
Section: Methodssupporting
confidence: 64%
“…Among ternary tetrelides, one of the most structurally complex family encompasses phases with the general composition RE 117 M 52+x Tt 112+y , where RE is a rare-earth metal, M is Cr, Fe, Co, or Ni, and Tt is Ge or Sn [46,47,[294][295][296][297][298][299][300][301][302][303][304][305][306]. All these compounds, despite small structural differences, crystallize in giant face-centered cubic unit cells with more than 1000 atoms.…”
Section: Tetrelides (Group 14)mentioning
confidence: 99%